Parametric analysis of a residential building with phase change material (PCM)-enhanced drywall, precooling, and variable electric rates in a hot and dry climate. (15th July 2018) - Wijesuriya, Sajith; Brandt, Matthew; Tabares-Velasco, Paulo Cesar
Highlights: Parametric analysis includes PCM location/properties, precooling, and convection regimes. PCM obtain higher savings in conjunction with forced convection. Optimal combination completely shifts cooling energy to off-peak period. Maximum cost savings up to 29% Energy cost savings depends on the ceiling fan efficiency. Abstract: Peak electric energy demand inflicts a great stress on the electric grid during the summer in the United States. With most years surpassing its previous year for the warmest year ever recorded, cooling requirements will continue to increase in the coming decades. Energy storage can potentially reduce electric demand. Among different technologies, phase change materials (PCMs) embedded in the building envelope have the potential to shift cooling energy demand away from peak hours. This study performs parametric analysis of PCMs in a relatively new home located in Phoenix, Arizona, USA. The analysis includes PCM location, PCM properties, precooling strategy, and an analysis of natural and forced convection models on the thermal behavior of the house. An extension of a standard forced convection model in EnergyPlus is used to represent the effects of a ceiling fan, which increases heat transfer at wall and ceiling surfaces and shortens the time needed to freeze or melt the phase change materials. Furthermore, the study discusses the use of appropriate setback temperatures to best utilize the PCMs. Overall, the optimal combination of PCMs, convection mode, and precooling schedule can completely shift cooling energy use during a three-hour demand period, producing maximum cost savings up to 29.4%, while increasing the occupant comfort.